A McKettrick Christmas [large type] - Miller, Linda Lael (Miller, Linda Lael. McKettricks of Texas., 2008)
Lizzie is bringing Whitley home for Christmas. He might seem a little too interested in the McKettrick money, but she's certain he cares for her deep down. When their train is halted by a massive avalanche, Dr. Shane takes charge, and fate has a surprise of its own.